Identification of Leishmania infantum and Leishmania braziliensis in captive primates from a zoo in Brazil - Guiraldi, Lívia M. [UNESP]; dos Santos, Wesley J. [UNESP]; Manzini, Suzane [UNESP]; Taha, Nur el H. A.; Aires, Isabella N. [UNESP]; Ribeiro, Emilly [UNESP]; Tokuda, Marcos; de Medeiros, Maria Izabel M.; Richini-Pereira, Virgínia B. [UNESP]; Lucheis, Simone B. [UNESP] (Wiley, 2022)
Wild nonhuman primates (NHP) are considered natural hosts of a protozoan parasite from the genus Leishmania, the etiological agent of leishmaniasis. It is important to study the population of this infectious agent in zoo animals to establish surveillance and control mechanisms in Sorocaba through the application of a One Health approach, this is where human–animal–environment health and disease interface and can aid in the protection of endangered species. This study aimed to identify Leishmania infantum and Leishmania braziliensis in NHP living in a city where leishmaniasis is endemic. DNA was extracted from 48 NHP and analyzed using polymerase chain reaction primers that are specific for the species L. infantum and L. braziliensis. The results of our research revealed the first report of L. infantum and L. braziliensis naturally infecting primates at Sorocaba zoo. One primate from the species Plecturocebus vieirai was positive for L. infantum and five primates (four Alouatta caraya and one Ateles chamek) were positive for L. braziliensis. This indicates a possible role of these animals on the maintenance of these parasites.
Keywords: leishmaniasis; monkey; one health; PCR; zoonosis